(untitled) (Revista de Medicina Clinica, 2020)
It is clear that this new entity called covid19, took us by surprise, for those same consequences of ignoring the degree of contagiousness, generated a rapid spread, affecting vulnerable people and the degree of transmission, was extremely high in health personnel, with the articles published today do not give much better guidance to take the pertinent measures and recommendations to try to reduce the spread of covid19. In this review we describe the proposals made by different authors, societies and international organizations in the management of patients with a need for a tracheostomy. Some precautionary measures are suggested in the care of the patient with a tracheostomy.